La Anatomia de la Ansiedad : Comprender y Superar la Repuesta de Nuestro Cuerpo al Miedo - Vora, Ellen ([Place of publication not identified] : Planeta Publishing, 2023)
"Anxiety affects more than forty million Americans-a number that continues to climb in the wake of the COVID-19 pandemic. While conventional medicine tends to view anxiety as a "neck-up" problem-that is, one of brain chemistry and psychology-the truth is that the origins of anxiety are rooted in the body."--
Includes bibliographical references and index.
Keywords: Anxiety; Anxiety -- Treatment; Mind and body; Ansiedad; Ansiedad -- Tratamiento; Mente y cuerpo; Self-help publications